The Award and final determination of the referees : respecting the claims of the Proprietors of the Kenebeck Purchase from the late colony of New-Plymouth, and the company holding under Clark and Lake, relative to the lands on each side Kenebeck River ([publisher not identified], 1757)
By mutual agreement, the dispute between the Clark and Lake Company and the Proprietors of the Kennebeck Purchase, commonly known as the Plymouth Company, was resolved by a committee of five lawyers, whose names are given above. Cf. Kershaw, Gordon E. The Kennebeck proprietors, 1749-1775, Somersworth, N.H., 1975, ch. VIII.